A Preliminary Study on the Selected Biochemical Parameters of Adolescents from Kopay Medical Officer of Health, Jaffna - Menaka, S.; Arasaratnam, V.; Surendrakumaran, R. (Postgraduate Institute of Science, University of Peradeniya, 2024)
Adolescence is the transitional stage of development between childhood and adulthood. It is a critical period for establishing healthy habits, including diet, exercise, and lifestyle choices. The study was aimed at determining the nutritional status of adolescents (from 17-19 years old) based on selected biochemical parameters from Kopay medical officer of health (MOH), Jaffna district. Data collection was made from 70 adolescents from Kopay MOH area. Blood samples were collected for the analysis of hematological indices by cyanmethemoglobin method and serum albumin concentration by calorimetric bromocresol green method. Ethical review for the study was obtained from the Ethics Review Committee, Faculty of Medicine, University of Jaffna. Out of the total 70 adolescents 38 were females (54.3%). Mean age of the male and female adolescents were 17.73 (±0.8) and 18.35 (± 0.7) in years respectively. Mean serum albumin concentrations of males and females were 4.048 (± 0.2) and 3.986 (± 0.2) g/dl respectively, and 3.13% (n=1) and 15.79% of (n=6) of the males and females respectively had protein deficiency. Mean haemoglobin (hb) concentration of the male adolescents was 13.72 (± 2.4) g/dl with the range from 7.2 g/dl to 16.9 g/dl the female adolescents was 12.23 (± 2.0) g/dl with range from 6.1 g to 16.1 g/dl and among them 37.14% (n=26) were with anemia while 7.7% (n=2) had severe anemia. The mean of HCT, MCV, MCH and MCHC levels of the male and female adolescents were 40.24% (±6.9), 85.95 fl (±8.4), 27.90 (±3.3) pg and 32.42 (±1.7) g/dl respectively. Of the total adolescents 3.13% (n=1) males and 10.5 % (n=4) females were affected with both iron deficiency anaemia and protein deficiency. Thus, the adolescents were more affected with iron deficiency anaemia than protein deficiency. The study revealed a prevalence of anaemia and protein deficiency among the adolescents (17-19 years) in the Kopay MOH area.
Keywords: Adolescents; Albumin; Anaemia; Haemoglobin; Nutritional status